EXISTENCE THEOREM FOR ORDINARY NONLINEAR DIFFERENTIAL EQUATIONS. - SALUNKHE, Dr.S.N. (IJRDO -JOURNAL OF MATHEMATICS, 2018)
In this article, an existence theorem for ordinary nonlinear differential equations with the periodic boundary value problem is proved under mixed generalized Lipschitz and caratheodory conditions for the aspects of solutions. Our result includes some known existence results for ordinary nonlinear differential equations with the periodic boundary value problems.